Prédire l’avenir ou relancer le devenir ? - Bérénice Palaric (Recherches Germaniques)
On the occasion of the centenary of their major works, the second volume of The Decline of the West and Der Historismus und seine Probleme (1922), this article aims to confront the thought of two significant intellectuals of the first years of the Weimar Republic: the neoconservative Oswald Spengler (1880-1936) and the liberal democrat Ernst Troeltsch (1865-1923). Starting from the provocation contained in the thesis of the “decline,” the analysis reconstructs their respective conception of history, of the West and of the democratization of Germany. The aim is to examine their antagonisms while highlighting their belonging to a common historical and discursive background. The formal motives that structure their argumentation present strong analogies, for instance the renewal of the philosophy of history and universal history, the criticism of Eurocentrism, belief in the ineluctability of democracy and the emphasis on its dangers, and the ambivalent use of conservatism in the legitimization of ideological positions.